Catenary Optics: Catenary Electromagnetics for Ultra‐Broadband Lightweight Absorbers and Large‐Scale Flat Antennas (Adv. Sci. 7/2019) - Huang, Yijia (Adv Sci (Weinh), 2019)
Catenary functions are exciting and fundamental building blocks in constructing various kinds of waves in subwavelength structures. In article number 1801691, Xiangang Luo and co‐workers propose a simple yet powerful approach to realize efficient design of metasurfaces inspired by catenary electromagnetics. By employing this methodology, flexible‐substrate‐based large‐scale broadband absorbers and flat antennas are experimentally achieved with lightweight properties and outstanding operation performances. [Image: see text]